Kuala Selangor Estuary Salinity Intrusion Modeling during Extreme Flood Events - Farhan Haron, Nuryazmeen; Tahir, Wardah; Wei-Koon, Lee; Mohd Ali, Siti Nurhayati; Sediqi, Mohammad Naser (Journal of Advanced Research Design, 2025)
The occurrence of extreme flood events causes flood plain inundation and sedimentation. In the estuary, these processes lead to salinity changes, which adversely affect the estuarine ecosystem. A shallow water model (SWM) had been used for the Selangor River estuary up to Kg. Asahan station, the limit of saline water intrusion. The performance of the model has been verified using two decades of observed data. The model was used to simulate flood events in Kuala Selangor to investigate salinity intrusion attributed to transverse flow during extreme flood events. Analysis shows that as the annual recurrence interval increases, the flood depth increases, but the salinity level reduces due to the dilution effect from the riverine fresh water inflow.